Flexible Vertical Photogating Transistor Network with an Ultrashort Channel for In‐Sensor Visual Nociceptor. (24th June 2021) - Feng, Guangdi; Jiang, Jie; Li, Yanran; Xie, Dingdong; Tian, Bobo; Wan, Qing
Abstract: Humans can clearly perceive surroundings efficiently while consuming little energy because of human intelligence and powerful vision system. Thus, it has been a long‐sought dream for human beings to build such an energy‐efficient artificial intelligent vision system with emerging devices. Unfortunately, a wearable optoelectronic device for visual nociceptor systems, regarded as a key bionic function to protect the vision, remains to be developed so far. Herein, using the vertical coplanar‐multiterminal flexible transient photogating transistor network with a 3 nm ultrashort channel, a wearable artificial vision system with painful‐perceptual abilities is successfully demonstrated for flexible electronic‐skin (e‐skin) applications. The device not only has the ability of ultrafast transient physical disappearance of only 60 s for information security but also establishes a flexible optical in‐sensor visual nociceptor (ISVN) e‐skin. The optical transition from short‐time memory to long‐time memory of visual memory is educed by a strong photogating effect, and the higher‐level‐graded optical painful alarm‐sensing system is also demonstrated by this flexible artificial e‐skin. Moreover, the proposed devices will achieve painful light sensitization under different spatiotemporal color patterns to avoid external secondary injuries. It provides a good opportunity for future intelligent e‐skin taking advantage of its intriguing visual pain‐perceptual abilities. Abstract : A retina‐inspired visual e‐skin system with pain‐perceptual abilities is successfully demonstrated using a flexible vertical coplanar‐multiterminal polyelectrolyte‐gated phototransistor network. The transition of visual memory is induced by the photogating effect, and the light‐painful sensitivity and perception abilities are also demonstrated. Most importantly, this device can achieve painful light sensitization under different spatiotemporal color patterns.